Soil biological communities and ecosystem resilience - Lukac, Martin; Grenni, Paola; Gamboni, Mauro (Springer, 2017)
This volume explores current knowledge and methods used to study soil organisms and to attribute their activity to wider ecosystem functions. Biodiversity not only responds to environmental change, but has also been shown to be one of the key drivers of ecosystem function and service delivery. Soil biodiversity in tree-dominated ecosystems is also governed by these principles, the structure of soil biological communities is clearly determined by environmental, as well as spatial, temporal and hierarchical factors. Global environmental change, together with land-use change and ecosystem management by humans, impacts the aboveground structure and composition of tree ecosystems. Due to existing knowledge of the close links between the above- and belowground parts of terrestrial ecosystems, we know that soil biodiversity is also impacted. However, very little is known about the nature of these impacts; effects on the overall level of biodiversity, the magnitude and diversity of functions soil biodiversity generates, but also on the present and future stability of tree ecosystems and soils. Even though much remains to be learned about the relationships between soil biodiversity and tree ecosystem functionality, it is clear that better effort needs to be made to describe and understand key processes which take place in soils and are driven by soil biota.
Includes index.
Keywords: Soil biodiversity -- Congresses.; elektronické knihy; electronic books